Information and Communication Technology Media Management in Improving the Quality of Learning in Vocational Middle School (SMK) - Prionggo Hendradi; Achmad Sanusi; Hanafiah; Hendi Suhendraya Muchtar (Journal of Islamicate Studies, 2022)
Information and Communication Technology (ICT) is currently experiencing very rapid development and has fundamentally brought significant changes in the acceleration and innovation of education. One of them is for the education system, especially distance education learning, namely ICT media management using the Learning Management System (LMS) where the concept is very influential on the quality of education. This is due to many things, including distance education learning (PJJ) with ICT media in the ICT media management system using LMS to improve the quality of learning in Vocational Schools (SMK Graphic Lektur and SMK Yadika 4) which are not maximized and inadequate so that the aim of improving the quality of education is to improve the quality of education. not achieved. This research resulted in a innovation (novalty), namely the development of the concept of an ICT media management model to improve the quality of learning in Vocational Schools which has implications for achieving quality graduates in Vocational Schools so that they are worthy of being recommended in Vocational Schools throughout Jabodetabek.